Natural flavonoids in Delonix regia leaf as an antimycobacterial agent: An in silico study - Tjitda Putra Jiwamurwa Pama; Nitbani Febri Odel; Mbunga Dominus; Wahyuningsih Tutik Dwi (Journal of the Serbian Chemical Society, 2023)
Multi-drug resistant (MDR) and extensively-drug resistant (XDR) as results of continuous use of antibiotics encourage the development of new antimycobacterial drugs. In this study, 13 flavonoid compounds from the flamboyant leaf plant were studied for their inhibitory properties of MtKasA, MtDprE and MtPank which are significant enzymes in Mycobacterium tuberculosis, as well as for their molecular docking, molecular dynamics and prediction of ADMET-drug likeness. The results of molecular docking studies revealed that compound F13 (apigenin) was the most potent compound because it was able to bind the most amino acids as indicated by the native ligand of each enzyme. Molecular dynamics studies showed that compound F13 forms a stable complex with MtKasA. The results of the ADMET-drug likeness analysis concluded that compound F13 was the most promising compound. Overall, compound F13 has the potential to be used as a treatment therapy against M. tuberculosis.